ULBP1 is induced by hepatitis C virus infection and is the target of the NK cell‐mediated innate immune response in human hepatocytes. Issue 3 (25th January 2018) - Dansako, Hiromichi; Imai, Hirotaka; Ueda, Youki; Satoh, Shinya; Wakita, Takaji; Kato, Nobuyuki
Abstract : Natural killer (NK) cells through their NK group 2 member D (NKG2D) receptors recognize NKG2D ligands such as UL16‐binding proteins (ULBPs) on virus‐infected cells and subsequently trigger the host innate immune response. In the present study, we demonstrated that hepatitis C virus (HCV) induced the cell surface expression of ULBP1 in human immortalized hepatocyte PH5CH8 cells and human hepatoma HuH‐7 cell‐derived RSc cells. Interestingly, NK cell line NK‐92 induced cytotoxicity and interferon‐γ mRNA expression and subsequently reduced the levels of HCV RNA replication during co‐culture with HCV‐infected RSc cells. From these results, we conclude that ULBP1 is a target of the NK cell‐mediated innate immune response in HCV‐infected human hepatocytes. Abstract : Cell‐surface expression of the NK group 2 member D ligand ULBP1 was increased by hepatitis C virus (HCV) in immortalized human hepatocytes and human hepatoma cells. Natural killer (NK) cell mediated‐cytotoxicity and interferon‐γ mRNA expression was enhanced towards HCV‐infected cells and subsequently inhibited viral replication. Our results suggest that NK cells trigger the host innate immune response through the recognition of ULBP1 on HCV‐infected hepatocytes.